The Influence of Papuan Folklore to Improve Speaking and Self-Confidence With Show and Tell Method in SMK Modellink Sorong - Janet Marlon Yoseph Marisan; Rizqi Claudia Wardani.H; Agus Setiawan (English Education Program Universitas Pendidikan Muhammadiyah Sorong, 2025)
The purpose of this study was to determine whether the integration of Papuan folklore could improve students’ speaking skills and self-confidence through the show and tell method at SMK Modellink Sorong. Speaking is widely recognized as one of the most challenging skills for EFL learners because it requires the simultaneous use of vocabulary, grammar, pronunciation, and fluency (Rizky & Suharmoko, 2019). In addition, affective factors such as self-confidence strongly influence students’ willingness to communicate (Akbari & Sahibzada, 2020). Preliminary classroom observations revealed that many students experienced hesitation, anxiety, and limited vocabulary when asked to speak in English. To address this issue, this study implemented culturally responsive instruction by integrating Papuan folklore into the show and tell learning method. The research employed a quantitative pre-experimental design using a one-group pretest–posttest model. The participants were 20 students of class X TKJ. Data were collected through speaking tests, self-confidence questionnaires, and classroom observations. Speaking performance was assessed based on comprehension, vocabulary, grammar, pronunciation, and fluency. The data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and a paired sample t-test with SPSS version 31. The findings showed that the significance value was 0.000 < 0.05, indicating a significant difference between pretest and posttest scores. The mean score increased from 49.15 to 68.70. Questionnaire results also showed that most students reached the confident category after the treatment. These findings suggest that Papuan folklore combined with the show and tell method is effective in improving both speaking performance and self-confidence among vocational high school students, although future studies with control groups are recommended.